Relationship between attitudes toward the effectiveness of vaccine, concerns about adverse reactions, and proactively taking SARS-Cov-2 vaccine for family among medical workers in Taizhou, China. (1st February 2022) - Luo, Chengwen; Zhang, Mei-Xian; Shi, Gui-Feng; Chen, Hai-Xiao; Tung, Tao-Hsin
ABSTRACT: Objectives: Concerns about the safety of the SARS-CoV-2 vaccine have been a stumbling block in the promotion of vaccination uptake. Although many studies have focused on the investigation of people's intention to receive the COVID-19 vaccine, little attention has been paid to the underlying mechanism. This study explored whether concerns about the adverse reactions to the vaccine mediated the relationship between attitudes toward the effectiveness of the vaccine and proactively taking the vaccine for family. Methods: Questionnaires were completed by 1, 673 (39.9%, 1673/4191) healthcare workers at Taizhou Hospital, Taizhou, Zhejiang, China. Among these, 1, 397 (83.5%) have received two doses of the SARS-Cov-2 vaccine. Mediation analysis approach was applied in this research. Results: Attitudes toward the effectiveness of vaccines were positively correlated with proactively taking the COVID-19 vaccine for family. Additionally, concerns about the side effects to the SARS-Cov-2 vaccine mediated the relationship between attitudes toward the effectiveness of vaccines and proactively taking vaccines for family. Conclusion: The findings imply inextricable relationships among attitudes toward the effectiveness of the SARS-Cov-2 vaccine, fears about side effects to vaccines, and taking vaccines for family. It further suggested that the importance of highlighting the safety of vaccine in promotion of vaccination uptake.